Relativistic Tests do not Falsify Euclidean 3-geometry of Continuous Space-matter - Bulyzhenkov, Igor (Relativistic Tests do not Falsify Euclidean 3-geometry of Continuous Space-matter, 2021)
Aligned polarization of quasars at megaparsec distances, correlated motion of galaxies, and entangled sub-organizations of cosmic distributions and living matter require nonlocal macroscopic physics within a joint framework with quantum mechanics. Recorded scattering and dissipative energy exchange in the laboratory created the pragmatic illusion of localized material bodies existing in empty space before and after the procedure of local measurements. This illusion was mathematically supported by the point mass model with alleged pulls from gravitational (negative, non-existent) energy densities. Einstein's General Relativity can be reformulated in metric terms of continuous mass-energy with positive (measurable) densities. The kinetic nature of distributed rest energy or its continuous mass density with local metric stresses disproves Newtonian gravitational fields as a conceptual carrier of pulling energy. This book develops new mathematics of geometrized inertial densities to explain the basic tests of Einstein's physics in terms of Cartesian matter-expansion with Euclidean three-dimensional space in curved spacetime. The distant pulls of Newtonian gravity are replaced by correlated metric stresses in the kinetic monism of nonlocally distributed mass-energy throughout the Universe.